(Pr0.75La0.25)0.7Sr0.3MnO3:Agx (0 ≤ x ≤ 0.25) polycrystalline ceramics with room-temperature TCR improvement for uncooled infrared bolometers. Issue 11 (1st August 2020) - Pu, Xingrui; Li, Hongjiang; Chu, Kaili; Duan, Yunbiao; Li, Zhidong; Liu, Xiang
Abstract: In this work, perovskite manganite (Pr0.75 La0.25 )0.7 Sr0.3 MnO3 :Ag x (PLSMO:Ag x, x  = 0, 0.05, 0.10, 0.15, 0.20 and 0.25) ceramics were successfully prepared by sol-gel route and solid-state reaction. The surface morphologies, peak temperature variation behaviors of temperature coefficient of resistivity ( TCR ), microstructural and electrical transport properties of all the specimens were analyzed by various testing methods like XRD, SEM, EDS, R-T and XPS. XRD Rietveld refinement data demonstrated that Mn–O bond length, Mn–O–Mn bond angles and the unit cell volume increased along with the rise in x . Consequently, the bandwidth describing the overlap between the O2 p and Mn3 d orbitals reduced, and this change further affected the electrical transport properties. Scanning electron microscopy (SEM) images indicated that silver was helpful in increasing the grain size. The metal-insulator transition temperature increased due to the enhancement in double exchange (DE) interaction. X-ray photoelectron spectroscopy (XPS) fitting data (percentage of Mn 4+ and O 2− ) along with XRD Rietveld refinement data confirmed the enhancement in DE interaction. The most remarkable thing was that the reduction in resistivity occurred gradually, which resulted in a significant improvement in the TCR . The TCR value achieved 11.35% K −1 with the peak temperature being 300.69 K (room-temperature ~ 300 K) at x  = 0.15. Obviously, obtaining a large room-temperature TCR value (≥10% K −1 ) in praseodymium perovskite oxides was encouraging since such results have not been explored previously. Overall, the proposed PLSMO:Ag0.15 ceramic with large room-temperature TCR value look prospective candidates for future advanced uncooled infrared bolometers.